Thyroid Storm in a Young Woman: A Clinical Case - Garlet, Cristiane Venturini; Tomitão, Isadora de Macedo; Delgado do Amaral, Kayque Wellek; Negrete Bomura, Tiffany Ayumi; Barbosa Lima, Ana Carla; Marques, Sellen Almeida; Manfredini, Rebecca Corrêa; Fortaleza de Melo, João Italo (International Journal of Innovative Research in Medical Science, 2020)
Thyroid storm is a rare condition, but it can be characterized as a threat to life. It presents as an increase in the functions of the thyroid gland due to dysfunction of the central nervous system. It is characterized by pyrexia, tachycardia, heart failure and alterations in the digestive system. The objective of this report is to describe the case of a young woman with no previously reported diseases, who was affected by the thyroid storm, without the presence of Graves' disease.